Perturbation of Hydrogen-Bonding Networks over Supported Lipid Bilayers by Poly(allylamine hydrochloride) - Dalchand, Naomi; Doğangün, Merve; Ohno, Paul E; Ma, Emily; Martinson, Alex B. F; Geiger, Franz M (The journal of physical chemistry. B, 2019)
Water is vital to many biochemical processes and is necessary for driving fundamental interactions of cell membranes with their external environments, yet it is difficult to probe the membrane/water interface directly and without the use of external labels. Here, we employ vibrational sum frequency generation spectroscopy to understand the role of interfacial water molecules above bilayers formed from zwitterionic (phosphatidylcholine) and anionic (phosphatidylglycerol, PG, and phosphatidylserine, PS) lipids as they are exposed to the common polycation poly(allylamine hydrochloride) (PAH) in 100 mM NaCl. We show that as the concentration of PAH is increased, the interfacial water molecules are irreversibly displaced and find that it requires 10 times more PAH to displace interfacial water molecules from membranes formed from purely zwitterionic lipids when compared to membranes that contain the anionic PG and PS lipids. This outcome is likely due to the difference in (1) the energy with which water molecules are bound to the lipid headgroups, (2) the number of water molecules bound to the headgroups, which is related to the headgroup area, and (3) the electrostatic interactions between the PAH molecules and the negatively charged lipids that are favored when compared to the zwitterionic lipid headgroups. The findings presented here contribute to establishing causal relationships in nanotoxicology and to understanding, controlling, and predicting the initial steps that lead to the lysis of cells exposed to membrane-disrupting polycations or to transfection.